Vertical handoff algorithms - A new approach for performance evaluation (2010)
A myriad of Vertical Handoff Algorithms (VHA) have been proposed by researchers and networks practitioners. These algorithms allow mobile terminals (MT) to maintain the network connection when they switch from one wireless network to another one. Given the amount of proposed VHA and the need for an objective assessment of these solutions different evaluation methodologies have been proposed, becoming the problem of evaluation of VHA in an interesting challenge. However, there is no consensus on how to evaluate performance of VHA. In this paper, we address this issue by proposing a new approach for evaluating the VHA, which is based on multi -criteria evaluation and criticality analysis - a specific concept taken from the operational reliability. The new approach allows evaluating VHA using measured values of some defined parameters, which can be obtained from simulating VHA on a network simulation tool (e.g. NCTUns, NS -2, OMNET++, among others) or generic software simulation tools (e.g. MATLAB). As a test of the new model, an evaluation of five VHA is presented